The Knowability Argument and the syntactic type-theoretic approach - Rosenblatt, Lucas Daniel (2013)
Recently, there have been some attempts to block the Knowability Paradox and other modal paradoxes by adopting a type-theoretic framework in which knowledge and necessity are regarded as typed predicates. The main problem with this approach is that when these notions are simultaneously treated as predicates, a new kind of paradox appears. I claim that avoiding this paradox either by weakening the Knowability Principle or by introducing types for both predicates is rather messy and unattractive. I also consider the prospect of using the truth predicate to emulate necessity, knowledge and other modal notions. It turns out that this idea works much better.